COMPARISON OF DIFFERENT TECHNIQUES FOR EVALUATION OF DOSE DISTRIBUTIONS IN RADIOTHERAPY USING RADIOCHROMIC EBT3 FILMS - Dufek, V; Horakova, I; Koniarova, I (Radiation protection dosimetry, 2019)
In radiotherapy, radiochromic films can be used for verification of delivery of dose distributions calculated by treatment planning systems. The main objective of this work was to compare three different techniques for evaluation of dose distributions for prostate cancer treatment plans using radiochromic EBT3 films. These techniques are: red channel evaluation taking into account only a response of irradiated film (R), red channel evaluation taking into account a response of unirradiated and irradiated film (Rcor) and multichannel evaluation in FilmQA software (RGB). Also comparison between film and MatriXX measurement was performed. Comparison showed that gamma analysis passing rates strongly depend on evaluation technique and on a model of scanner for digitizing films. The highest gamma passing rates were obtained with red channel evaluation taking into account a response of unirradiated and irradiated film using Epson V750 scanner (Rcor) and multichannel evaluation in FilmQA using Epson 11000XL scanner.
Keywords: algoritmy; Algorithms; kalibrace; filmová dozimetrie; lidé; Radiotherapy Dosage; Phantoms, Imaging; celková dávka radioterapie; mužské pohlaví; nádory prostaty; záření gama; Film Dosimetry; Radiotherapy, Intensity-Modulated; Prostatic Neoplasms; fantomy radiodiagnostické; Calibration; Humans; radioterapie s modulovanou intenzitou; plánování radioterapie pomocí počítače; Gamma Rays; Male; Radiotherapy Planning, Computer-Assisted